Pembuatan minyak plastik dengan metode destilasi bertingkat - Setiawan, Rahmady; Dharma, Untung Surya; Andriyansyah, Nopri; irawan, Dwi; yanto, Repki (ARMATUR : Artikel Teknik Mesin & Manufaktur, 2020)
Waste is unwanted residual material and is no longer used after the end of a process. garbage that cannot be decomposed (undegradable) which is rubbish that cannot rot like plastic, becomes a problem in itself, so much garbage is disposed of every day by humans becomes a very complex problem that is certainly very disturbing to the environment and ecosystem, therefore management is efficient and precise will be very helpful in efforts to reduce waste in the environment, by conducting a multilevel distillation process it is hoped that waste will become a fuel which is certainly more useful. The types of waste used in this study include: PET (Polyethylene terephthalate, HDPE (High Density Polyethylene), PVC (Polyvinyl Chloride), LDPE (Low Density Polyethylene, PP (Polypropylene), PS (Polystyrene). The purpose of this study is to know the value of Viscosity, Density, and Calorific Value of plastic oil which is processed by the distillation method stratified at temperature variations.From the tests conducted using temperature variations, the density value of oil sample C which is distilled at a temperature of 450o C in both tubes has the highest value, namely 0.844 gr / cm3.The highest heating value is in PP (Polyprophylene) oil of 43808.1 Joules / gram. The oil viscosity of sample C has the highest value of 1.9200 cSt.